Research on Cross-Domain Study Curricula in Cyber-Physical Systems: A Case Study of Belarusian and Ukrainian Universities - Anatolijs Zabasta; Joan Peuteman; Nadezda Kunicina; Volodymyr Kazymyr; Sergey Hvesenya; Andrii Hnatov; Tatsiana Paliyeva; Leonids Ribickis (MDPI AG, 2020)
The increasing importance of continuingly complex Cyber-Physical Systems (CPS) challenges and encourages universities worldwide to organize up-to-date CPS oriented educational programs. The Erasmus+ project "CybPhys" aims to support CPS oriented educational programs in Belarus and Ukraine. We put forward a hypothesis that the educational situation, training opportunities, situation of the labor market, and general economic development are related to each other and can vary depending on the region. In order to validate our hypothesis and to provide input to curricula modernizations, an in-depth study in the form of surveys was conducted in the years 2019-2020. The results of the study showed that the differences between the perceptions of stakeholders in different regions of one country were more significant than the deviations between the global evaluation marks obtained from Belarusian and Ukrainian respondents. In order to increase the synergy of the CybPhys partners, the transdisciplinary and T-shape skills approaches are introduced to the education programs of the partner's universities. An innovative ICT based teaching and learning environment and associated teaching methodologies will be developed. The research provides valuable input to the development of industry and research-oriented cross-domain study programs in Cyber-Physical Systems focused on the needs of Belarusian and Ukrainian industries.